One-pot three-component sulfone synthesis exploiting palladium-catalysed aryl halide aminosulfonylation - Richards-Taylor, C; Blakemore, D; Willis, M (2014)
A palladium-catalysed aminosulfonylation process is used as the key-step in a one-pot, three-component sulfone synthesis. The process combines aryl-, heteroaryl- and alkenyl iodides with a sulfonyl unit and an electrophilic coupling fragment. The sulfonyl unit is delivered in the form of an aminosulfonamide, which then serves as a masked sulfinate. The sulfinate is combined, in situ, with an electrophilic coupling partner, such as a benzylic, allylic or alkyl halide, an electron-poor arene, or a cyclic epoxide, to provide the corresponding sulfone products in good to excellent yields. The mild reaction conditions and use of commercially available reaction components allows the easy preparation of a broad range of sulfones featuring a variety of functional groups. The process obviates the need to employ thiol starting materials, and oxidative operations. © 2013 The Royal Society of Chemistry.